Karakter Eğitimi: Dün, Bugün ve Yarın / Character Education: Yesterday, Now and Tomorrow - SIRRI, Vahide; Mehmedoğlu, Ali Ulvi (Journal of History Culture and Art Research, 2015)
Character Education: Yesterday, Now and Tomorrow Abstract This study aims to describe the character education, to identify implemented character education activities in the world and Turkey, and bring recommendations to the character education studies in Turkey. In the study, the literature regarding the character education has been examined and the character education has been questioned in this regard. The general principles which are important for character education programs has found out as a result of the analysis of the documents. In this framework, some suggestions have been put forward for character education studies in Turkey. In the result of the examinations, it has been revealed that the character education studies have had a very old background, as a concept emerged in the US for the first time and spread to other countries in the world, and have been gaining importance day by day. Although it is extremely difficult to talk about an applying character education program in Turkey yet, the conducted researches implement an increasing interest in this field. Karakter Eğitimi: Dün, Bugün ve Yarın Öz Bu çalışmada amaç karakter eğitimini açıklamak, dünyada ve Türkiye’de uygulanan karakter eğitimi çalışmalarını belirlemek ve Türkiye’deki karakter eğitimi çalışmalarına öneriler getirmektir. Yöntem olarak doküman incelemesi yöntemi kullanılmıştır. Çalışmada karakter eğitimiyle ilgili olarak alandaki literatür incelenmiş, karakter eğitimi bu çerçevede sorgulanmıştır. Dokümanların analizi sonucunda karakter eğitimi programları için önemli olan genel ilkeler çıkarılmıştır. Bu çerçevede Türkiye’deki karakter eğitimi çalışmaları için öneriler ortaya konmuştur. Yapılan incelemeler sonucunda karakter eğitimi çalışmalarının tarihinin çok eski olduğu, kavram olarak ise ilk defa ABD’de ortaya çıktığı ve buradan diğer dünya ülkelerine yayıldığı ve gün geçtikçe önem kazandığı ortaya çıkmıştır. Henüz Türkiye'de uygulanan bir karakter eğitimi programı olduğundan bahsetmek oldukça güç olsa da yapılan araştırmalar bu alana ilginin olduğunu göstermektedir